Talking through walls: mechanisms of lateral root emergence in Arabidopsis thaliana - Vilches-Barro, Amaya; Maizel, Alexis (Current opinion in plant biology, 2015)
Lateral roots are formed postembryonically and determine the final shape of the root system, a determinant of the plants ability to uptake nutrients and water. The lateral root primordia are initiated deep into the main root and to protrude out the primary root they have to grow through three cell layers. Recent findings have revealed that these layers are not merely a passive physical obstacle to the emergence of the lateral root but have an active role in its formation. Here, we review examples of communication between the lateral root primordium and the surrounding tissues, highlighting the importance of auxin-mediated growth coordination as well as cell and tissue mechanics for the morphogenesis of lateral roots.
Published online: 30 October 2014
Gesehen am 23.06.2017